2003
DOI: 10.1897/1551-5028(2003)022<0661:aomdop>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Monitoring Data of Pesticide Residues in Surface Waters Using Partial Order Ranking Theory

Abstract: In this investigation, a new and simple way to analyze, interpret, and generalize monitoring data of occurrence of pesticide active ingredients in surface waters was developed. The occurrence is quantified using the variables frequency of detection and the concentration level. These two parameters are associated with basically different ecotoxicological effects; for example, a high frequency of detection may be related to bioaccumulation problems, while the level of concentration also controls the acute toxico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Beigel et al (1999) demonstrated that the persistence of the fungicide triticonazole increased with application rate. Similar studies with pesticides have revealed that application rate is a dominant factor in determining pesticide concentration in surface waters (Sorensen et al 2003).…”
Section: Introductionmentioning
confidence: 72%
“…Beigel et al (1999) demonstrated that the persistence of the fungicide triticonazole increased with application rate. Similar studies with pesticides have revealed that application rate is a dominant factor in determining pesticide concentration in surface waters (Sorensen et al 2003).…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, in our study we tested the appropriateness of a concept of partial order theory, namely the Hasse Diagram Technique (HDT) (Brüggemann et al 2001a), to analyze patterns in the changes of species communities, in this case along an urban-rural gradient. HDT has already been successfully used in environmental science and chemistry (Halfon and Reggiani 1986;Brüggemann et al 1999;Klein 2000;Felinks 2001;Brüggemann et al 2001b;Carlsen et al 2001;Lerche et al 2002;Brüggemann et al 2003a;Brüggemann et al 2003b;Sørensen et al 2003;Thinh et al 2004;Simon et al 2004a;Simon et al 2004b). However, as far as we know, no such formalized data analysis, including the use of explanatory background information, has been applied to date in the context of gradient analysis.…”
Section: Introductionmentioning
confidence: 99%
“…If the model ranking is able to reproduce the experimental ranking, then other compounds that do not poses an experimental value can be assigned a position in the ranking and then their experimental properties can be predicted. A type of similarity index necessary to define for QSAR based on POR is the modified Tanimoto index T (0,0), reflecting the percentage of rankings in the model that can be found in the experimental data [64]. It is defined as…”
Section: Qsar Based On Hasse Diagramsmentioning
confidence: 99%